Westonci.ca makes finding answers easy, with a community of experts ready to provide you with the information you seek. Connect with a community of experts ready to provide precise solutions to your questions on our user-friendly Q&A platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

If [tex]$x=5^{1 / 3}-5^{-1 / 3}$[/tex], prove that [tex]$x^3+3x=\frac{24}{5}$[/tex].

Sagot :

Certainly! Let's start with the expression given:

[tex]\[ x = 5^{1/3} - 5^{-1/3} \][/tex]

We need to prove that:

[tex]\[ x^3 + 3x = \frac{24}{5} \][/tex]

### Step 1: Calculate [tex]\( x^3 \)[/tex]

First, let's cube both sides of the equation [tex]\( x = 5^{1/3} - 5^{-1/3} \)[/tex]:

[tex]\[ x^3 = \left(5^{1/3} - 5^{-1/3}\right)^3 \][/tex]

Using the binomial theorem for the expansion of [tex]\( (a - b)^3 \)[/tex]:

[tex]\[ (a - b)^3 = a^3 - 3a^2b + 3ab^2 - b^3 \][/tex]

Setting [tex]\( a = 5^{1/3} \)[/tex] and [tex]\( b = 5^{-1/3} \)[/tex]:

[tex]\[ x^3 = \left(5^{1/3}\right)^3 - 3\left(5^{1/3}\right)^2\left(5^{-1/3}\right) + 3\left(5^{1/3}\right)\left(5^{-1/3}\right)^2 - \left(5^{-1/3}\right)^3 \][/tex]

Simplifying powers of [tex]\( 5 \)[/tex]:

[tex]\[ x^3 = 5 - 3 \cdot 5^{1/3 - 1/3} + 3 \cdot 5^{1/3 - 2/3} - 5^{-1} \][/tex]

Since [tex]\( 5^{0} = 1 \)[/tex]:

[tex]\[ x^3 = 5 - 3 \cdot 1 + 3 \cdot 5^{-1/3 - 1/3} - 5^{-1} \][/tex]

[tex]\[ x^3 = 5 - 3 + 3 \cdot 5^{-1} - 5^{-1} \][/tex]

Since [tex]\( 5^{-1} = \frac{1}{5} \)[/tex]:

[tex]\[ x^3 = 5 - 3 + 3 \cdot \frac{1}{5} - \frac{1}{5} \][/tex]

Combining the constants:

[tex]\[ x^3 = 5 - 3 + \frac{3}{5} - \frac{1}{5} \][/tex]

[tex]\[ x^3 = 2 + \frac{2}{5} \][/tex]

Converting to a common denominator:

[tex]\[ x^3 = \frac{10}{5} + \frac{2}{5} \][/tex]

[tex]\[ x^3 = \frac{12}{5} \][/tex]

### Step 2: Calculate [tex]\( 3x \)[/tex]

Next, we need to find:

[tex]\[ 3x = 3 \left( 5^{1/3} - 5^{-1/3} \) \][/tex]

Since we just need the value of [tex]\( x \)[/tex]:

[tex]\[ 3x = 3 \left( 5^{1/3} - 5^{-1/3} \) \][/tex]

### Step 3: Sum these results

Now we need to sum [tex]\( x^3 \)[/tex] and [tex]\( 3x \)[/tex]:

[tex]\[ x^3 + 3x = \frac{12}{5} + \frac{12}{5} \][/tex]

Combining the terms:

[tex]\[ x^3 + 3x = \frac{24}{5} \][/tex]

Thus, we have proven that:

[tex]\[ x^3 + 3x = \frac{24}{5} \][/tex]
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.